Lactoferrin is a dynamic protein in human melioidosis and is a TLR4-dependent driver of TNF-α release in Burkholderia thailandensis infection in vitro. - Shelton W Wright; Lara Lovelace-Macon; Deirdre Ducken; Sarunporn Tandhavanant; Prapit Teparrukkul; Viriya Hantrakun; Direk Limmathurotsakul; Narisara Chantratita; T Eoin West (Public Library of Science (PLoS), 2020)
Melioidosis is an often-severe tropical infection caused by Burkholderia pseudomallei (Bp) with high associated morbidity and mortality. Burkholderia thailandensis (Bt) is a closely related surrogate that does not require BSL-3 conditions for study. Lactoferrin is an iron-binding glycoprotein that can modulate the innate inflammatory response. Here we investigated the impact of lactoferrin on the host immune response in melioidosis. Lactoferrin concentrations were measured in plasma from patients with melioidosis and following ex vivo stimulation of blood from healthy individuals. Bt growth was quantified in liquid media in the presence of purified and recombinant human lactoferrin. Differentiated THP-1 cells and human blood monocytes were infected with Bt in the presence of purified and recombinant human lactoferrin, and bacterial intracellular replication and cytokine responses (tumor necrosis factor-α (TNF-α), interleukin-1β and interferon-γ) were measured. In a cohort of 49 melioidosis patients, non-survivors to 28 days had significantly higher plasma lactoferrin concentrations compared to survivors (median (interquartile range (IQR)): 326 ng/ml (230-748) vs 144 ng/ml (99-277), p<0.001). In blood stimulated with heat-killed Bp, plasma lactoferrin concentration significantly increased compared to unstimulated blood (median (IQR): 424 ng/ml (349-479) vs 130 ng/ml (91-214), respectively; p<0.001). Neither purified nor recombinant human lactoferrin impaired growth of Bt in media. Lactoferrin significantly increased TNF-α production by differentiated THP-1 cells and blood monocytes after Bt infection. This phenotype was largely abrogated when Toll-like receptor 4 (TLR4) was blocked with a monoclonal antibody. In sum, lactoferrin is produced by blood cells after exposure to Bp and lactoferrin concentrations are higher in 28-day survivors in melioidosis. Lactoferrin induces proinflammatory cytokine production after Bt infection that may be TLR4 dependent.